Mitral annulus disjunction is highly prevalent in patients with Marfan syndrome and Loyes-Dietz syndrome. (25th November 2020) - Chivulescu, M; Krohg-Sorensen, K; Scheirlynk, E; Lindberg, B; Dejgaard, L; Lie, O; Helle-Valle, T; Skjolsvik, E; Aabel, E; Hunt, T; Estensen, M; Edvardsen, T; et al.
Abstract: Background: Mitral valve prolapse is a common finding in patients with Marfan and Loyes-Dietz syndrome. Mitral annulus disjunction (MAD), an atrial displacement of the hinge point of the mitral valve, has previously been associated with non-syndromic MVP and life-threatening ventricular arrhythmias. Purpose: We aimed to assess the prevalence of MAD in patients with Marfan and Loyes-Dietz syndrome and relate the presence of MAD to mitral valve prolapse. Methods: We included genotype positive patients with Marfan and Loyes-Dietz syndrome, and patients with Marfan syndrome fulfilling Revised Ghent Criteria. Mitral valve prolapse was defined as superior mitral leaflets' displacement ≥2mm beyond the mitral annulus. MAD was diagnosed by echocardiography and quantified as the distance from the ventricular myocardium to the hinge point of the posterior mitral leaflet (Figure, left panel). Results: We included 111 patients with Marfan syndrome and 66 patients with Loyes-Dietz syndrome (age 26 [IQR, 13–39] years, 53% male). Mitral valve prolapse was observed in 54 (31%) and MAD in 74 (42%) patients. Longitudinal MAD distance was 8 (IQR, 6–10) mm. Forty-six (85%) patients with mitral valve prolapse had concomitant MAD, p<0.001 (Figure, right panel). Conclusion: Mitral valve prolapse was observed in one third of patients with Marfan and Loyes-Dietz syndrome. MAD was highly prevalent and found in 42% of all patients and in 85% of those with mitral valve prolapse. Presence of mitral valve prolapse in Marfan and Loyes-Dietz syndrome should raise awareness of MAD which may be of importance in follow-up and monitoring of these patients. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Health Authority of South Eastern Norway